A needs assessment of the integration of domestic violence and substance abuse services for women - Hunt, Tammy Lynn (2007)
The purposes of the study was to conduct a needs assessment in order to assess the problem of substance abuse among the women in domestic violence agencies. Data was collected by surveys that were mailed out to the directors of domestic violence agencies within two counties, San Bernardino and Los Angeles, California